Evolutionary rescue via transgenerational plasticity: Evidence and implications for conservation. Issue 4 (1st February 2021) - Harmon, Emily A.; Pfennig, David W.
Abstract: When a population experiences severe stress from a changing environment, evolution by natural selection can prevent its extinction, a process dubbed "evolutionary rescue." However, evolution may be unable to track the sort of rapid environmental change being experienced by many modern‐day populations. A potential solution is for organisms to respond to environmental change through phenotypic plasticity, which can buffer populations against change and thereby buy time for evolutionary rescue. In this review, we examine whether this process extends to situations in which the environmentally induced response is passed to offspring. As we describe, theoretical and empirical studies suggest that such "transgenerational plasticity" can increase population persistence. We discuss the implications of this process for conservation biology, outline potential limitations, and describe some applications. Generally, transgenerational plasticity may be effective at buying time for evolutionary rescue to occur. Abstract : The flow of information in transgenerational plasticity: Environmental cues received by parents may induce a change in phenotype through plasticity (different shading). Processed information can then be used to transmit a cue to the individual's offspring and may induce a change in the phenotype of offspring or later generations through transgenerational plasticity. Research Highlights: Transgenerational plasticity can allow populations to persist in changed environments, thereby buying time for evolutionary rescue. A review of traits and taxa show promise for the application of transgenerational plasticity to conservation methods.